Development of sustainable concrete using iron ore tailings as sand replacement - Shettima Umara Ali, 1969- , author; Mohd. Warid Hussin, 1950- , supervisor; Yusof Ahmed, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2017